Standing on our own feet? Opportunities and risks of European self-defence - Eckhard Lübkemeier (Stiftung Wissenschaft und Politik (SWP), 2021)
Only a Europe that provides for its own defence can be a fully sovereign Europe. As is the case for the US, Europe would have to be capable of protecting its core security interests without depending on its transatlantic partner. Structural incentives as well as recent developments militate in favour of establishing such intra-NATO status parity. Structurally, unilateral dependence, even among friends, comes at a price. This timeless incentive is reinforced by recent developments: the demise of the old West, with or without Trump; China's twofold challenge; an emerging Sino-American rivalry; a resurgent Russia; the new world disorder; Macron's offer to his European partners. European self-defence has to meet four key requirements: broader and greater European integration, sufficient military capabilities, effective strategy, and political leadership. Defence autonomy requires an independent nuclear deterrent capability. In the case of the EU, neither primary deterrence, reserved for a single state, nor extended deterrence, such as that provided by the United States, would be adequate. Instead, Europe would have to create a novel type of 'integrated deterrence'. Underpinned by a solid community of solidarity and trust, this would be based on French nuclear forces, with the French president maintaining exclusive decision-making authority. Germany and France would have to seize the initiative by 'taking their bilateral relations to a new level', as stated in the Aachen Treaty of January 22, 2019. They would have to lead by example, bring about the progressive integration of their armed forces and an alignment of their strategic cultures. This would demand a great deal of Germany in terms of defence spending and redefining its 'culture of military restraint'. To initiate such a process of rethinking and repositioning will require an open-minded debate on the role of the military for a Europe that 'takes its fate into its own hands' (Chancellor Angela Merkel).
Keywords: 320